2018
DOI: 10.1128/jcm.00560-18
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Xpert MTB/RIF, Xpert Ultra, and Abbott RealTi m e MTB for Diagnosis of Pulmonary Tuberculosis in a High-HIV-Burden Setting

Abstract: More sensitive tests are needed for the diagnosis of smear-negative and HIV-associated tuberculosis. This study compares the sensitivities and specificities of three molecular tests, namely, the Xpert MTB/RIF test, the Xpert Ultra (Ultra), and RealTime MTB (RT-MTB), in a high HIV prevalence setting. Symptomatic adults were recruited from three outpatient sites, and each provided 4 sputum specimens. The diagnostic performance of Xpert MTB/RIF, Ultra, and RT-MTB was evaluated, with culture as a reference standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
5
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 19 publications
12
52
5
5
Order By: Relevance
“…1) [13]. Similar results have been obtained in a high-HIV-burden setting reporting a gain in sensitivity for Ultra of þ11.7% in adult HIV patients whereas no gain was observed in HIV-negative patients [19].…”
Section: Sensitivity In Hiv Positive Patientssupporting
confidence: 84%
See 1 more Smart Citation
“…1) [13]. Similar results have been obtained in a high-HIV-burden setting reporting a gain in sensitivity for Ultra of þ11.7% in adult HIV patients whereas no gain was observed in HIV-negative patients [19].…”
Section: Sensitivity In Hiv Positive Patientssupporting
confidence: 84%
“…For instance, Berhanu and colleagues compared the performance of Ultra with the Real-Time MTB assay (RT-MTB) (Abbott, Des Plaines, USA) [43]. Sensitivity of Ultra and RT-MTB on the same specimens were 88.9% and 77.8%, respectively [19]; in contrast, Xpert and RT-MTB displayed similar performances [44]. It would be beneficial to have more studies that compare the performance of Xpert and Ultra with the other tests that target the same DNA sequences, in particular for the diagnosis of extrapulmonary tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…On 11 October 2018, we performed a literature search specifically for studies that evaluated Xpert Ultra, but did not identify any additional studies. Following this search and after the end date for data analysis, we identified one additional study ( Berhanu 2018 ). Although not included in the main sections of this review, we provide a brief summary of this study here.…”
Section: Discussionmentioning
confidence: 99%
“…Although not included in the main sections of this review, we provide a brief summary of this study here. Berhanu 2018 compared Xpert MTB/RIF and Xpert Ultra in 237 participants with presumptive tuberculosis who were evaluated at three outpatient clinics in South Africa. Similar to the results in Dorman 2018 , this multicentre study found that Xpert Ultra yielded higher sensitivity at 89% (78% to 96%), compared to Xpert MTB/RIF sensitivity of 82% (70% to 91%), but lower specificity at 96% (92% to 98%) compared to Xpert MTB/RIF specificity of 100% (98% to 100%).…”
Section: Discussionmentioning
confidence: 99%
“…GeneXpert Ultra (the next generation assay) has been shown to overcome some of the shortcomings of GeneXpert MTB/RIF as it showed improved sensitivity of 95% and negative predictive value of 99% in a more recent study on HIV positive adults with TBM (16). However, concerns over lowered specificity and positive predictive value compared to GeneXpert MTB/RIF need to be allayed by prospective testing in a large population including children and those that are HIV-uninfected (16,18,19). The main common limitation to the above-described tests is the difficulty in obtaining the diagnostic sample (CSF) due to the need for more invasive sampling methods and low yields of mycobacteria obtained from childhood CSF samples, as a result of the paucibacillary nature of the disease.…”
Section: Introductionmentioning
confidence: 99%